Effects of the performance level and the FIFA "11" injury prevention program on the injury rate in Italian male amateur soccer players - Gatterer, H.; Ruedl, G.; Faulhaber, M.; Regele, M.; Burtscher, M. (The Journal of Sports Medicine and Physical Fitness, 2012)
AIM: Soccer is characterized by high injury rates that necessitate interventions for its reduction. The "11" is a multi-modal preventive program that was developed to reduce injury rate. However, outcomes on the effectiveness of the program are not unambiguous and data for the largest group at risk (i.e., male adult amateur players) are missing. The study aims to assess the injury rate in male adult amateur soccer players of different levels and to evaluate the effectiveness of the prevention program the "11". METHODS: Three amateur soccer teams participated in the study during the first round of a competition season. Two teams played at a regional level (6th Italian league) and one team at a provincial level (7thItalian league). The regional league is of a higher skill level compared to the provincial league. Duration and frequency of training and match sessions and the occurrence of time-loss injuries were recorded. One team of the 6th league performed an injury prevention program. RESULTS: The total injury rate for the intervention and the control team in the 6th league was 3.3 (CI 0.7-5.9) and 4.3 (CI 1.3-7.3) injuries/1000 h, respectively (P=0.841). The 6th league control team tended to have a lesser injury rate compared to the 7th league team (P=0.081). The relative risk was 2 fold higher in the 7th compared to the 6th league team (P=0.0285 one tailed). CONCLUSION: Present results show that injury rate in amateur soccer depended rather on the skill level than the prevention program. In this study the prevention program the "11" was not shown to be highly effective in soccer player of intermediate level (i.e., 6th Italian league).